Welfare Reform: Consequences for the Children - Marianne Simonsen; Lars Skipper; Jeffrey Andrew Smith (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
This paper uses register-based data to analyze the consequences of a recent major Danish welfare reform for children's academic performance and well-being. In addition to work requirements, the reform brought about considerable reductions in welfare transfers. We implement a comparative event study that contrasts outcomes for individuals on welfare at the time of reform announcement before and after the implementation of the reform with the parallel development in outcomes for an uncontaminated comparison group, namely those on welfare exactly one year prior. Our analysis documents that mothers' propensity to receive welfare decreased somewhat as a consequence of the reform, just as we observe a small increase in hours worked. At the same time, we do not detect negative effects on children's short-run academic performance. We do find small negative effects on children's self-reported school well-being and document substantial upticks in reports to child protective services for children exposed to the reform.
Keywords: I38; J13; J22; 330; welfare reform; child outcomes; Denmark